Markedly elevated procalcitonin due to anaphylactic shock, a case report. Issue 9 (September 2022) - Altermanini, Mohammad; Hijazi, Mohamad; Aboursheid, Tarek; Alhammad, Muhammad Firas; Ali, Khaled; Tayar, Elias; Jasim, Ramsey
Abstract: Procalcitonin (PCT) is a well-known biomarker that is directly connected to bacterial infection especially when it reaches significantly high levels. It is extremely rare to be witnessed in non-bacterial infections such as viral or parasitic. It may be elevated in other conditions such as trauma and autoimmune diseases. We present a rare case of a young gentleman, who had an extremely high PCT level that appeared to be a result of anaphylaxis due to worm infestation. Abstract : Procalcitonin; Anaphylaxis; Shock; Colonoscopy; Worm infestation.